Financial Ratio Analysis in DU PONT SYSTEM to Measure Financial Performance PT. Terminal Teluk Lamong - Fittrofin Amalia Farisa; Iis Dewi Ratih; Niluh Shanthi Sekarini (Institut Teknologi Sepuluh Nopember, 2020)
Companies are defined as organizational units that use various factors of production and produce goods and services to be sold to households, other companies or the government in a profit-oriented manner. In this global era, competition among actors is increasingly competitive. In this research will be conducted to measure the company's financial performance using ratio analysis in the DuPont System at PT. Teluk Lamong Surabaya Terminal in the period 2016 to 2018. The DuPont System can identify the cause of the inefficiency of a company based on its financial statements. The purpose of this financial ratio analysis is to see and evaluate the company's current and future financial condition. This study aims to determine the results of financial performance at the company PT. Teluk Lamong Surabaya Terminal in the period 2016 to 2018.